Digital economy: innovation and technologies - Rumyk, Ihor; Румик, Ігор Іванович (OU Scientific Center of Innovative Research, 2023)
The digital economy is a type of economy where the key factors (means) of production are digital data: numerical, textual, etc. Their use as a resource makes it possible to significantly increase the efficiency, productivity, value of services and goods, to build a digital society. Digitization is one of the main factors in the growth of the world economy in the next 5-10 years. In addition to the direct productivity gains that companies get from digital technologies, there is a chain of indirect benefits of digitalization, such as saving time, creating new demand for new goods and services, new quality and value. Nowadays, the level of development of digital technologies plays a critical role in the competitiveness of countries and economic unions. The Eurasian Economic Union (EAEU) considers the transition to a digital economy to be the key driver of economic growth. In recent years, EAEU member states have made significant progress in many areas of digital development. The prospects and relevance of digital development of the economies of the EAEU member states were reflected in the Main Directions of the Digital Agenda of the EAEU by 2025, where digital transformation is emphasized as a key factor of development. Harmonization of efforts in the joint implementation of initiatives and projects of the Digital Agenda of the EAEU will allow the expansion of the capabilities of member states, citizens and business entities not only within the EAEU, but also in foreign markets. The effectiveness of joint actions of member states within the Digital Agenda depends on the successful development of their own economies. The implementation of the Digital Agenda will require the creation of digital platforms, network infrastructures, enabling initiatives and projects, building partnerships with those who have chosen the path of digital transformation. Digital transformation means the integration of digital technologies into all areas of business. This integration leads to fundamental changes in the way citizens, enterprises and organizations act, how they provide value for themselves, their employees, customers, partners, achieving their own and common economic and social goals faster, cheaper and with new quality. Digital technologies include the Internet of Things, robotics and cyber systems, artificial intelligence, big data, paperless technologies, additive technologies (3D printing), cloud and fog computing, unmanned and mobile technologies, biometrics, quantum technologies, identification technologies, blockchain, etc. Digitization should be considered as a tool, not as an end in itself. With a systemic state approach, digital technologies will stimulate the creation of jobs, increase productivity, rates of economic growth and the quality of life of citizens.
Keywords: digital economy; digital technologies; transformation; financial inclusion factors; digital culture; digital innovation; Industry 4.0